The lichenized fungi of the genus Glyphis in Veracruz, Mexico - Guzmán-Guillermo, Jorge; Barrera-Bernal, Clementina; Llarena-Hernández, Régulo Carlos (Instituto de Ecología, A.C., 2021)
Background and Aims: The Graphidaceae family is considered one of the most representative of lichenized fungi, both in Mexico and in the world. Approximately 175 of its species have been recorded in Mexico. The objective of this study is to carry out a taxonomic review of Glyphis in Veracruz, through the analysis of literature and material collections from the tropical zone of the elevation gradient on the "Cofre de Perote", Veracruz, Mexico. Methods: Microlichens were collected from localities in tropical ecosystems of the altitudinal gradient of the "Cofre de Perote", Veracruz, Mexico, in cloud forest and tropical dry forest. The material was processed and deposited in the XALU herbarium and analyzed using conventional lichenology techniques for morphology and macrochemistry. Databases and previous works were consulted to know the distribution of Glyphis species in Mexico and the world; moreover, we provide a taxonomic key of the species discussed here. Key results: Glyphis scyphulifera and G. atrofusca are reported for the first time in the state of Veracruz and G. substriatula is cited for the first time in Mexico. A key is included to determine the known Glyphis species for Mexico. Conclusions: According to the collections carried out in the tropical zone of the altitudinal gradient of the "Cofre de Perote", Veracruz, Mexico, it was found that four of the five species of Glyphis accepted in the world inhabit this place, being Glyphis cicatricosa and G. scyphulifera throughout the sampled part of the gradient, while G. atrofusca and G. substriatula are restricted to low elevations.